Pulmonary thromboembolism due to immune-mediated hemolytic anemia in a cat: A serial study of hematology and echocardiographic findings - Yoshida, Tomohiko; Mandour, Ahmed S.; Sato, Manami; Hirose, Miki; Kikuchi, Rina; Komiyama, Norihiro; Hendawy, Hanan A.; Hamabe, Lina; Tanaka, Ryou; Matsuura, Katsuhiro; Uemura, Akiko (Frontiers in Veterinary Science, 2022)
Pulmonary thromboembolism (PTE) secondary to immune-mediated hemolytic anemia (IMHA) is rarely diagnosed in cats. In this report, a 3-year-old cat was referred to our private hospital with dyspnea, anorexia, and anemia. On the thoracic radiography, cardiac enlargement and pulmonary edema were noted. Echocardiography revealed right ventricular and right atrium enlargement with mild tricuspid regurgitation (tricuspid regurgitation velocity 3.28 m/s). A thrombus was recognized in the main pulmonary artery on the right parasternal short-axis view. Blood examination suggested regenerative anemia and autoagglutination. The findings suggested immune-mediated hemolytic anemia and PTE. Antithrombotic therapy (dalteparin) and immunosuppressive therapy (prednisolone) were administered under oxygen supplementation in the ICU cage. After treatment, regenerative anemia and right-heart failure were improved. During follow-up, the cat remained hemodynamically stable, and the owner reported no cardiac-related clinical signs. Further blood examination confirmed the anemia was improved. Prednisolone was discontinued on Day 56, and the cat continues in good health, administered only mycophenolate mofetil. The clinical outcome of PTE secondary to the IMHA throughout 100 days of periodical observation was reported.